Taking back the tech: an analysis of take back the S 2015 twitter campaign during 16 days of activism against gender violence - Mabaso, Samukelisiwe (Centre for Film and Media Studies, 2019)
The online abuse and harassment of women through hate speech is a growing problem. This study explores responses to abuse of women on Twitter, by analysing the tactics employed by the feminist network, Take Back The Tech! (TBTT) to combat online abuse through their global 16 Days of Activism Against Gender Violence campaign. This study employs various analytical frameworks including feminism, intersectionality, counterpublics, and agenda-setting to investigate TBTT’s tweets and other Twitter users’ responses to the campaign, as suggested by Twitter replies and mentions. During their campaign, TBTT used online activism for both advocacy and mobilisation. Their campaign also worked to empower marginalised voices through the sharing of survivor stories while embracing global dialogue. Calls to action were a fundamental tactic employed by TBTT during the campaign. These calls to action encouraged both online and offline action. TBTT highlighted the need to share stories of strategies for countering violence against women (VAW), to organise offline by arranging meetings to discuss technology-related violence, to transform tools for digital safety, and to encourage followers to make their own digital safety roadmaps. The majority of TBTT’s tweets were original tweets and TBTT also frequently retweeted other users’ tweets throughout their campaign. Through this act of agenda-setting, TBTT aimed to raise public awareness of technology-related VAW. Hashtags enabled TBTT to keep track of the discussion, gauge the progress and success of their campaign, and it also allowed Twitter users to follow and contribute towards the hashtagged conversation. Hashtags were also an effective method of networkbuilding which connected TBTT to other Twitter campaigns dealing with similar issues. These hashtags linked specific TBTT campaigns to broader feminist concerns, while also building connections with feminist counterpublics. TBTT used Twitter for agenda-setting by linking to external media in their tweets. Including these URLs was an effective way of pointing followers to additional information such as their own website, commercial media websites, and websites of feminist and women’s organisations. Furthermore, TBTT overcame Twitter’s 140-character limit and included additional information by using images such as pixel-art characters, memes, infographics, and photos of campaigners’ work. The majority of users who engaged with TBTT during 16 Days did so via mentions while only a few engaged via replies. Thus, despite the active campaigning by TBTT, the Twitter data suggests a relatively low level of active engagement. It is unclear from the available data whether this limited response reflects weaknesses in the campaign, the potentially stifling effect of online abuse or whether followers might have preferred private engagement. Thus, while empowering women, engaging with them and sharing information, tools, resources and tips in order to put online abuse on the public agenda, TBTT’s campaign also highlights the continued importance of “safe” spaces for feminists.